1997
DOI: 10.1007/s002940050206
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of the IR in the chloroplast genomes of buckwheat species is due to incorporation of an SSC sequence that could be mediated by an inversion

Abstract: The chloroplast genomes in buckwheat species contain large inverted repeats which are at least 4 kbp longer than the majority of those in land plants. The length of the buckwheat inverted repeats was attributable to an additional region located adjacent to the borders of the small single-copy region. We have cloned and sequenced a 5. 2-kbp SmaI fragment corresponding to this extra region in the inverted repeats. A homology search revealed that the sequence of the SmaI fragment is highly homologous to one side … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 11 publications
1
17
2
Order By: Relevance
“…Expansion of the IR into the SSC region is much less common, and only a few angiosperm families exhibit this phenomenon, including Campanulaceae (Cosner et al 1997; Haberle et al 2008; Knox and Palmer 1999), Geraniaceae (Chumley et al 2006; Palmer et al 1987), and Polygonaceae (Aii et al 1997; Logacheva et al 2008). Earlier investigations of one or two plastid genomes of Poaceae (Hiratsuka et al 1989; Maier et al 1995; Prombona and Subramanian 1989) identified expansion of the IR into the SSC region resulting in the duplication of rps15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expansion of the IR into the SSC region is much less common, and only a few angiosperm families exhibit this phenomenon, including Campanulaceae (Cosner et al 1997; Haberle et al 2008; Knox and Palmer 1999), Geraniaceae (Chumley et al 2006; Palmer et al 1987), and Polygonaceae (Aii et al 1997; Logacheva et al 2008). Earlier investigations of one or two plastid genomes of Poaceae (Hiratsuka et al 1989; Maier et al 1995; Prombona and Subramanian 1989) identified expansion of the IR into the SSC region resulting in the duplication of rps15 .…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that rates of sequence evolution may be correlated to genomic changes in grass plastid genomes. It should be noted that after the divergence of the grasses no major genomic changes occurred aside from minor expansions of the IR region, a very common process that accounts for size variation in plastid genomes throughout angiosperms (Aii et al 1997; Goulding et al 1996; Plunkett and Downie 2000) including the monocots (Wang et al 2008). …”
Section: Discussionmentioning
confidence: 99%
“…However, the conventional circular map does summarize many of the heritable structural features of the genome correctly. Among plant lineages that retain both copies of the IR, the sizes and boundaries of these regions, relative to the adjacent LSC and SSC, have been modified in various groups (e.g., Goulding et al, 1996; Aii et al, 1997; Plunkett and Downie, 2000; Perry et al, 2002; Stefanović and Olmstead, 2005; Wang et al, 2008).…”
Section: Plastid Genome Structurementioning
confidence: 99%
“…For example, the unusual triple-sized expansion of the Geranium IR was hypothesized as an outcome of inversion due to recombination between homologous dispersed repeats [16]. Similarly, the at least 4 kb expansion of the IR in buckwheat ( Fagopyrum esculentum ) cpDNA was also considered to be associated with an inversion [17]. …”
Section: Introductionmentioning
confidence: 99%